The frequency and management of seizures during psychological treatment among patients with psychogenic nonepileptic seizures and epilepsy. (25th March 2018) - Kemp, Steven; Graham, Christopher D.; Chan, Rebecca; Kitchingman, Hayley; Vickerman, Kirsty; Reuber, Markus
Summary: Objective: Growing evidence suggests that psychological treatments are effective for improving outcomes in both epilepsy and psychogenic nonepileptic seizures (PNES). However, the risk of in‐session seizures may cause concerns about safety and about seizures disrupting treatment. This study explores the risk of in‐session seizures in patients with epilepsy and those with PNES, the timings of seizures during psychological therapy, and the responses of therapists to seizures. Methods: Consecutive patients with epilepsy or PNES attending 2 neurology centers in the United Kingdom for psychological treatment to help with their seizure disorders were studied. Information about seizures during outpatient psychological therapy sessions was gathered using a 12‐item pro forma. Results: Ninety‐seven patients with epilepsy and 195 with PNES were evaluated. One in 32 patients with epilepsy and 1 in 8 with PNES had at least 1 in‐session seizure. A seizure occurred in 1 in 136 treatment sessions provided to patients with epilepsy, and 1 in 36 sessions provided to those with PNES. The risk of in‐session seizures was significantly greater in patients with PNES than in patients with epilepsy (odds ratio [OR] 4.4, 95% confidence interval [CI] 1.3‐15.2). Seizures tended to occur in the first half of treatment programs and individual sessions and only disrupted sessions briefly. Only one patient with PNES required in‐patient observation not involving overnight admission. Significance: In‐session seizures do occur and are much more common in patients with PNES than in those with epilepsy. Seizures rarely caused major disruption to psychological treatment, and could almost invariably be managed by the treating therapist without help from additional medical staff. Nonetheless, this research suggests that psychological therapy providers should anticipate the occurrence of in‐session seizures and have safe management plans in place. The greater frequency of in‐session seizures in PNES may add to our understanding of the mechanisms triggering these seizures.